2021
DOI: 10.48550/arxiv.2111.03557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reaching for the Edge I: Probing the Outskirts of Massive Galaxies with HSC, DECaLS, SDSS, and Dragonfly

Jiaxuan Li,
Song Huang,
Alexie Leauthaud
et al.

Abstract: The outer light (stellar halos) of massive galaxies has recently emerged as a possible low scatter tracer of dark matter halo mass. To test the robustness of outer light measurements across different data sets, we compare the surface brightness profiles of massive galaxies using four independent data sets: the Hyper Suprime-Cam survey (HSC), the Dark Energy Camera Legacy Survey (DECaLS), the Sloan Digital Sky Survey (SDSS), and the Dragonfly Wide Field Survey (Dragonfly). We use customized pipelines for HSC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
(164 reference statements)
1
2
0
Order By: Relevance
“…However, Ragusa et al [150] conclude that the ICL colors g − r ∼ 0.7 mag and r − i ∼ 0.4 mag are consistent with the stellar population synthesis of intermediate-mass (M = 10 10 − 10 11 M ) galaxies without clear traces of dust, besides contaminations from Galactic cirrus at λ = 100 µm. It is worth noting that the averaged radial profiles in HCG 86 look similar (although obviously brighter) to the ones inferred for galaxy clusters [151,152], with the floor at µ ∼ 30 mag arcsec −2 strongly contaminated by the Galaxy cirrus [153][154][155]. A clear observational evidence of the virialization can be recognized in the image of the cluster CL0024+17 on Figure 6 obtained at the Large Binocular Telescope (LBT) by Giallongo et al [156]: in the lower panel, a concentration of the ICL toward the apparent cluster center of mass is observable.…”
Section: Tidal and Ram-pressure Strippingsupporting
confidence: 64%
“…However, Ragusa et al [150] conclude that the ICL colors g − r ∼ 0.7 mag and r − i ∼ 0.4 mag are consistent with the stellar population synthesis of intermediate-mass (M = 10 10 − 10 11 M ) galaxies without clear traces of dust, besides contaminations from Galactic cirrus at λ = 100 µm. It is worth noting that the averaged radial profiles in HCG 86 look similar (although obviously brighter) to the ones inferred for galaxy clusters [151,152], with the floor at µ ∼ 30 mag arcsec −2 strongly contaminated by the Galaxy cirrus [153][154][155]. A clear observational evidence of the virialization can be recognized in the image of the cluster CL0024+17 on Figure 6 obtained at the Large Binocular Telescope (LBT) by Giallongo et al [156]: in the lower panel, a concentration of the ICL toward the apparent cluster center of mass is observable.…”
Section: Tidal and Ram-pressure Strippingsupporting
confidence: 64%
“…7. Trujillo et al (2021) Li et al (2021) robustly evaluated the depth of these data and suggested that both HSC and DECaLS can achieve a surface brightness limit of μ r ∼ 28-29 mag arcsec −2 if customized pipelines are applied. 9.…”
Section: Merritt Et Al (2016) Investigated Eight Nearby Milkymentioning
confidence: 99%
“…Detailed kinematic analysis of the hydrodynamical simulations of cluster formation could be tremendously helpful for providing insight to the growth of the BCG sphere of influence, as well as an indirect check of the physical link between 𝑟 𝑠 and 𝑅 SOI . Observationally, our work can be easily extended to the larger cluster catalogues (Zou et al 2021;Wen & Han 2021;Yang et al 2021) and deeper photometry (Huang et al 2021;Li et al 2021) from current stage-III imaging surveys. Future ground-based and space missions like the LSST, Euclid, Roman, and CSST with even larger cluster samples, deeper photometry, and sharper shear measurements will greatly enhance our capability of seeing cluster formation through the diffuse light.…”
Section: Discussionmentioning
confidence: 95%